Comparison of Mitigation Strategies to Reduce Acrylamide in Prepared Maillard Model Systems - Aziz, Mahwash; Pasha, Imran; Anjum, Faqir Muhammad; Mahr-un-Nisa (Pakistan Journal of Nutrition, 2013)
Maillard model systems were prepared by using asparagine and glutamine as amino acids and glucose and fructose as reducing sugars. Acrylamide is the toxic compound that is produced during Maillard reaction among amino acids and sugars. So, in the current study, various mitigation strategies were utilized in these model systems to reduce the toxic effects of acrylamide. These mitigation strategies include vacuum treatment, application of calcium chloride as a cation and utilization of pectin. Afterward, acrylamide concentration was determined in these model systems by Gas Chromatography-mass Spectrometry (GC/MS) technique and progressive decrease was observed in acrylamide content by using different treatments. Maximum acrylamide concentration was observed in control i.e., 22.37±1.9 μg/g while minimum concentration (3.51±0.5 μg/g) was recorded in pectin-treated model system. Data pertaining to utilization of model system for acrylamide analysis by GC/MS indicated that model systems affected the acrylamide concentration momentously. Maximum acrylamide concentration (11.33±8.3 μg/g) was observed in Glucose-Asparagine model system, whilst minimum concentration (9.63±8.1 μg/g) was examined in Fructose-Glutamine model system. Consequently, pectin as a hydrocolloid reduced the higher content of acrylamide in comparison with vacuum treatment and calcium chloride.